Studi Komparasi Pengelolaan Dana Wakaf di KSPPS BMT Daerah Istimewa Yogyakarta - Achiria, Siti; Priyadi, Unggul (Fakultas Syariah IAIN Purwokerto, 2019)
In a provision of Law No. 41 of 2004 concerning Waqf, it is mentioned that the management of waqf is performed by nadzir, whether individual, organization, or legal entity. One of Islamic financial institutions that can manage waqf is KSPPS BMT with its role in social function (al-mÄl). Although some KSPPS BMTs have managed waqf fund, in reality, not all of them are registered in Indonesian Waqf Agency (BWI). In fact, license as nadzir is mandatory for whoever managing waqf. This study aimed to: 1) Revealing the differences and similarities of KSPPS BMT registered and not registered in BWI Center; 2) Describing the implications of the differences. This study was conducted using a qualitative method that involved KSPPS BMT waqf fund managers in Special Region of Yogyakarta and concludes that the differences are found in terms of legality, reports of waqf fund management and supervision by the BWI which is the fundamental for all waqf manager institutions. In addition, the similarities could be found in the collection, empowerment, and distribution of waqf fund. The differences between KSPPS BMTs registered and not registered in BWI have implications on some parties, including BWI, KSPPS BMT, and wÄqif (person performing waqf).